2017
DOI: 10.15376/biores.12.3.6283-6297
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Pressure Treatment on Poplar Wood: Density Profile, Mechanical Properties, Strength Potential Index, and Microstructure

Abstract: The density profile, mechanical properties, strength potential index, and microstructure changes of hybrid poplar were investigated before and after high-pressure (HP) treatments. The results of density profile indicated that a high uniform density distribution was developed inside the pressurized wood samples. The mechanical properties results showed that the HP treatments significantly increased (P < 0.05) the modulus of elasticity (MOE), the modulus of rupture (MOR), and the Brinell hardness (BH) of the den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 21 publications
1
15
0
1
Order By: Relevance
“…The process of softening is known as a pretreatment and combined with following mechanical pressing, achieving better compressing result. The thermo-mechanical densification [3][4][5], thermal-hydromechanical [6][7][8], hygro-mechanical steam treatment [9,10], mechanical-microwave treatment [11], and highpressure treatment [12,13] were developed to manufacture densified wood, in which the thermal-hydro is the most common and simplest pretreatment method currently. The cell walls of wood would be swelled by water although it cannot penetrate into crystalline region of cellulose.…”
Section: Introductionmentioning
confidence: 99%
“…The process of softening is known as a pretreatment and combined with following mechanical pressing, achieving better compressing result. The thermo-mechanical densification [3][4][5], thermal-hydromechanical [6][7][8], hygro-mechanical steam treatment [9,10], mechanical-microwave treatment [11], and highpressure treatment [12,13] were developed to manufacture densified wood, in which the thermal-hydro is the most common and simplest pretreatment method currently. The cell walls of wood would be swelled by water although it cannot penetrate into crystalline region of cellulose.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, with a decrease of board thickness and increase in CR, the density of the treated board increased significantly (p < 0.05) by 55.6%, 86.7%, 91.1%, 102% and 113% at 25 MPa, 50 MPa, 75 MPa, 100 MPa and 125 MPa, respectively. In our preliminary experiments, density was observed to decrease when pressure level exceeded 150 MPa [21]. These results indicate that HP densification for wood densification improves compression effects up to a certain pressure level gradually compressing the void spaces in the boards after which the degree of densification will be small.…”
Section: Densification Effects On Thickness Density and Mechanical Smentioning
confidence: 65%
“…This advantage makes HP-densified wood attractive for long-term indoor use when the environment relative humidity (RH) is low and the climate is relatively stable. Moreover, results showed that HP densification could make the densities of Chinese fir wood/poplar/paulownia wood to increase 2-3 times within 5 min [20,21,23]. This treatment is shown to be universally effective for various low-density species of wood.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations